The Effects of the Murdoch-Integrated Instruction with Graphic Organizer on Reading Comprehension in and Attitude Toward English Learning of Mathayom Suksa 6 Students - Singto, Ratchaneekorn; Ngamnin, Suthathip (Journal of Graduate Research, 2021)
The objectives of this research were to compare the reading comprehension of Mathayomsuksa 6 students before and after learning by Murdoch integrated approach with graphic organizer, to compare their reading comprehension after learning through the approach against the 70% criterion from the total scores, and to explore the students’ attitude toward learning English by utilizing the approach. The cluster random sampling method was applied to select the sample group of 35 Mathayom Suksa 6 students at Banphotphisaiphithayakhom School. The research instruments consisted of the lesson plans with the integration with the approach, the English comprehension test, and the attitude assessment toward English learning. The data were statistically analyzed for mean, standard deviation, and t-test dependent. The research results revealed that the student’s reading comprehension after learning through the approach was higher and it was higher than the 70% criterion. Their attitude toward English learning was at the highest level.